In Uzbekistan, The Press Is The Main Symbol Of A Democratic Society - Mamatov Ganisher Sapievich (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
This article analyzes the role and significance of the press in Uzbekistan's democratic society. Particular attention is paid to the role of mass media in implementing public oversight within the framework of the Law "On Public Oversight" adopted in 2018. The press is viewed as an important tool for fostering freedom of speech, openness, and civil society.